Non-transparency in real estate markets: a graphical solution - DOI: 10.5752/P.2316-1752.2011v18n22p8 - Weise, Andreas Dittmar; Littge, Lothar (Cadernos de Arquitetura e Urbanismo, 2012)
Real estate speculation has faced a recent problem caused by non-transparency in the property markets. Only a good base of information, transparency, gives the municipality the possibility to react to crisis, panics and real estate speculations. A possible way to provide transparency is to include in this map information about the old and updated values, number of transactions and the visualization of real estate speculation. Visualization of real estate speculation in the Standard Ground Value Map can give more transparency into the property markets, to their partners, supports the departments for a sustainable development of cities and to minimize the risk of a real estate speculation.